Estación Autosostenible Para La Clasificación Y El Aprovechamiento De Residuos En La Ciudad De Villavicencio (Meta) - Cipagauta Cortes, Larry Leonardo (Universidad Antonio Nariño, 2023)
This work proposes the architectural design of a selfsustainable station for the classification and use of solid waste in the city of Villavicencio (Meta), as a determination in the contribution of architecture projects that contribute to the management of urban solid waste with the potential to be reincorporated in the useful life cycle. One of the greatest challenges in cities around the world and particularly in Latin America is t he proper handling of materials once they have reached their useful life. In view of the commitments made by the 2021 agenda and the sustainable development goals. This despite the fact that architecture advances at a slightly slower pace with respect to t he events that affect society, nevertheless, it is feasible to establish the incorporation of raw materials and practices of saving resources and energy within the built environment. Socially, it is possible that architecture is a catalyst for the differen t actors around recycling and a space for education and acculturation in good environmental practices in the urban environment.